Conservation Status of Medicinal Plants from Papua and West Papua Province (Indonesia) - Anshary Maruzy; Rohmat Mujahid (Department of Forest Resources Conservation and Ecotourism - IPB University, 2019)
Research on Medicinal Plants and Jamu (RISTOJA) in of Papua and West Papua provinces was conducted in November-December 2012 and May 2017 using the purposive sampling and snowball method. The purpose of the review in this paper is to find out the patterns and trends in species used, and to discuss the factors that cause the vulnerability of declining plant species due to harvest pressure. In this paper, RISTOJA’s data is primary data and a review of the data is carried out by searching literature online and offline. From the results of RISTOJA in Papua and West Papua (Western New Guinea) in 2012 and 2017, there were 2929 numbers of medicinal plants, and it is estimated that from the 2929 numbers there were 983 species of medicinal plants, and from the estimated 983 species of medicinal plants there were 444 species of medicinal plants not yet identified, because most species do not have generative parts and there are 529 medicinal plants identified to species level (2.1% of the total flora of Papua and West Papua). From these data, one species of medicinal plants was included in the category of Critically Endangered (0.19%), two species of Endangered (0.38%), and four species of Vulnerable (0.76%), two species Near Threatened (0.38%), 61 species of Least Concern (11.53%), six species of Data Deficient (DD). Threatened status is more commonly found in species recorded as harvested by traditional healer not from gardens (forests and others). Thus, the continuous exploitation of harvests from the forest and the wildlife can lead to an increase in the future Red List status of some species which are at risk threatened condition. Keywords: IUCN, medicinal plants, Papua, RISTOJA, Western Papua